Meningkatkan Hasil Belajar PAK dengan Model Problem Based Learning Fase B Kelas 4 SDN 101990 Bangun Purba - Nika Frenti Damanik; Dicky Aprianto; Hedwigis Dian Permatasari (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
In the Kurikulum Merdeka, teachers have the flexibility to choose various teaching tools so that learning can be adjusted to the learning needs and interests of students. However, in the process, there are often various problems, one of which is a learning model that tends to be monotonous, namely lectures and assignments. This research aims to provide inspiration in the form of a Problem Based Learning learning model as an innovative effort to improve student learning outcomes both from cognitive and affective aspects. This research is carried out in two cycles, where each cycle includes planning, implementation, observation, and reflection stages. The data collected were in the form of cognitive learning outcomes through written tests, and observation sheets to observe affective learning outcomes. The results show that the application of the PBL model significantly improves student learning outcomes, which can be seen in the improvement graph from cycle I to cycle II. There are many innovative and creative learning models today, teachers should not stop learning to try and apply learning models to achieve the learning goals themselves.